Two new quill mite species of the family Syringophilidae (Acari: Prostigmata) parasitising the house sparrow Passer domesticus (L.) (Aves: Passeriformes) - Skoracki, Maciej; Sikora, Bozena (Zootaxa, 2014)
Two new quill mite species of the family Syringophilidae, Picobia passeri sp. nov. and Krantziaulonastus dubinini sp. nov., are described from quills of the body feathers of the house sparrow Passer domesticus (L.) (Passeriformes: Passeridae) from the European part of Russia.